Double walled carbon nanotubes promote the overproduction of extracellular protein-like polymers in Nitzschia palea: An adhesive response for an adaptive issue. (July 2015) - Verneuil, Laurent; Silvestre, Jérôme; Randrianjatovo, Irina; Marcato-Romain, Claire-Emmanuelle; Girbal-Neuhauser, Elisabeth; Mouchet, Florence; Flahaut, Emmanuel; Gauthier, Laury; Pinelli, Eric
Abstract: The present study assessed the effects of double-wall carbon nanotubes (DWCNTs) dispersed in the presence of a realistic concentration of natural organic matter (NOM, 10 mg L −1 ) on the benthic diatom Nitzschia palea using toxicity tests and quantitative/qualitative extracellular polymeric substances (EPS) assays. No toxic effect was observed. A growth delay was measured after 48 h of exposure to concentrations of DWCNTs ranging from 1 mg L −1 (∼29%) to 50 mg L −1 (∼84%). Extracellular carbohydrates and proteins were extracted using a sequential multi-methods protocol to collect soluble, hydrophobic and ion-bridged extracellular polymeric substances (EPS). Extracted EPS were analyzed by colorimetric assays and size exclusion chromatography. The results highlighted a higher EPS concentration in exposed cultures that was primarily caused by an overproduction of protein-like polymers (protein or glycoproteins, PLPs). Such EPS overproduction and increase in proteins/carbohydrates ratio can partially explain the observed growth inhibition. EPS were preferentially extracted using hydrophobic conditions and were mainly composed of PLPs with either low (10 kDa) or high (174 kDa) molecular weights. These data highlights the affinity between DWCNTs and EPS, which is primarily driven by both physical and hydrophobic interactions. This indicates that N. palea can respond to DWCNTs by forming an EPS network optimized for adhering to and efficiently wrapping DWCNTs.